Faktor Risiko Terjadinya Pneumonia Pada Balita Di Puskesmas Sruweng Kabupaten Kebumen - Falah, Yanuar Fajrul; Suhartono, Suhartono; Adi, Mateus Sakundarno; Mukhibin, Akhmad (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background: Pneumonia causes 23% of deaths in children under five and about 1.17 million deaths in toddlers worldwide. The Sruweng Health Center in Kebumen Regency in the last five years has experienced a fluctuating trend of pneumonia cases and infant deaths due to pneumonia in 2020 and 2024 with one case each.Methods: Using a case control study with a ratio of 1:1. The total sample was 150 (75 samples for each group). Cases are based on positive clinical symptoms who has been diagnosed by a doctor. Controls were selected using simple random sampling. Interviews and observations using questionnaires to collect the data. Data analysis was carried out univariately with frequency distribution tables, bivariate with chi square test, and multivariate with binary logistic regression test.Results: The difference in the proportion of family smoking behavior in the case group was higher (57.3%) than the control group only (3.33%). The final results were multivariate with binary logistic regression tests there were three significant variables, namely smoking behavior (OR= 3.7 ; 95% CI= 1.68-8.54; p= 0.001), waste burning behavior (OR= 2.4 ; 95% CI= 1.17-5.14 ; p= 0.017), and use of firewood (OR= 2.4 ; 95% CI= 1.13-5.21 ; p= 0.022).Conclusion: Smoking behavior is the main risk factor for the triggering of pneumonia in toddlers at the Sruweng Public Health Center, Kebumen Regency.Keywords: Pneumonia, Toddlers, Risk Factor, Kebumen Regency